Voices Welcomes Interviews - Stachyra, Krzysztof (Voices: A World Forum for Music Therapy, 2010)
As you can see our interview Voices’ section is bigger and bigger and it makes us more and more satisfied. You can read about world Music Therapy Conferences and music therapists working in the different parts of the world. At present, we are preparing a new interview “series” about a number of historically important music therapists whom many of us knew and worked with but there is a risk that the next generation will not know. You can help us in the development of the world music therapy community's knowledge about interesting well-known music therapists and lesser-known but interesting music therapists or music healers, by interviewing them. We would also welcome historical information about the development or transformation of music therapy in your region.